Downregulation of adenosine and adenosine A1 receptor contributes to neuropathic pain in resiniferatoxin neuropathy. Issue 8 (August 2018) - Kan, Hung-Wei; Chang, Chin-Hong; Lin, Chih-Lung; Lee, Yi-Chen; Hsieh, Sung-Tsang; Hsieh, Yu-Lin
Abstract : Abstract: The neurochemical effects of adenosine signaling in small-fiber neuropathy leading to neuropathic pain are yet to be explored in a direct manner. This study examined this system at the level of ligand (through the ectonucleotidase activity of prostatic acid phosphatase [PAP]) and adenosine A1 receptors (A1Rs) in resiniferatoxin (RTX) neuropathy, a peripheral neurodegenerative disorder that specifically affects nociceptive nerves expressing transient receptor potential vanilloid type 1 (TRPV1). We conducted immunohistochemistry on dorsal root ganglion (DRG) neurons, high-performance liquid chromatography for functional assays, and pharmacological interventions to alter PAP and A1Rs in mice with RTX neuropathy. In DRG of RTX neuropathy, PAP(+) neurons were reduced compared with vehicle-treated mice ( P = 0.002). Functionally, PAP ectonucleotidase activity was consequently reduced (ie, the content of adenosine in DRG, P = 0.012). PAP(+) neuronal density was correlated with the degree of mechanical allodynia, which was reversed by intrathecal (i.t.) lumbar puncture injection of recombinant PAP with a dose-dependent effect. Furthermore, A1Rs were downregulated ( P = 0.002), and this downregulation was colocalized with the TRPV1 receptor (31.0% ± 2.8%). Mechanical allodynia was attenuated in a dose-dependent response by i.t. injection of the A1R ligand, adenosine; however, no analgesia was evident when an exogenous adenosine was blocked by A1R antagonist. This study demonstrated dual mechanisms of neuropathic pain in TRPV1-induced neuropathy, involving a reduced adenosine system at both the ligand (adenosine) and receptor (A1Rs) levels. Abstract : This study demonstrates that functional prostatic acid phosphatase is required for maintaining the balance of cellular adenosine analgesia in systemic small-fiber neuropathy.